The Effect of Intermittent Fasting and Exercise on Body Composition, Antioxidant Capacity, and Blood Parameters in Obese Rats - Tatar, Tuğba; Tek, Nilüfer Acar (FapUNIFESP (SciELO), 2023)
Abstract This study aimed to examine the effects of exercise, intermittent fasting, and combining two methods on body weight, adipose tissue, lipids, and glucoregulator and antioxidant parameters. 90 day-old male rats were randomly divided into 5 groups of 6 rats each. The groups consist of rats with normal body weight-sedentary (C), obese-sedentary (O), obese-intermittent fasting only (IF), obese-exercise (swimming) only (E), and obese-intermittent fasting together with exercise (IFE). For 8 weeks (1. phase), 1 group was fed with standard pellets (2.7 cal/g). The other 4 groups were fed with a high-fat diet (4.496 cal/g) to develop obesity. Then for 8 weeks (2. phase), all rats feeding standard pellets were exercised and/or done intermittent fasting. There was no significant difference in body weight at the beginning of the study. The change in body weight was significantly higher in C than IFE, and E. Fasting blood glucose was higher in IF and IFE. Oxidative stress index (OSI) was lower in IF and IFE. Also, paraoxonase 1 (PON1) decreased in IFE. The fat cells' diameters of IF or E were lower than O but higher than C. The fat cell diameters of IFE were smaller than C. In conclusion, a combination of intermittent fasting and exercise in obese individuals caused reduced body weight, fat cell size, and oxidative stress. Besides, it caused increased fasting blood glucose, different effects on blood lipids, and decreased PON1. Thus intermittent fasting can be suggested by considering its positive and negative aspects and keeping it under follow-up.
Keywords: Intermittent fasting; Obesity; PON1; Exercise; TP248.13-248.65; Antioxidant capacity; Biotechnology; 2. Zero hunger